2019
DOI: 10.21595/jve.2018.19779
|View full text |Cite
|
Sign up to set email alerts
|

Joint parameter identification, vibration and noise analysis of gearbox

Abstract: A certain type of gearbox is investigated for the problem that the stiffness and damping of bearings are difficult to be accurately determined and then affect the analysis of vibration and noise of gearbox. Firstly, a coupled dynamic lumped parameter model of three-stage helical gear system with consideration of bearing stiffness, bearing damping, and transmission error is established. The modal parameters of gear system are obtained by using the experimental modal analysis method with single-input and multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The possibilities for theoretical and experimental research of transmissions and gearboxes are presented in a considerable number of publications. The most widely used experimental methods, described in [9] and [10], are based on the experimental determination of vibrations.…”
Section: Investigating the Possibilities For Improving The Operationa...mentioning
confidence: 99%
“…The possibilities for theoretical and experimental research of transmissions and gearboxes are presented in a considerable number of publications. The most widely used experimental methods, described in [9] and [10], are based on the experimental determination of vibrations.…”
Section: Investigating the Possibilities For Improving The Operationa...mentioning
confidence: 99%
“…Ren et al [3] proposed a gear-housingfoundation coupled impedance model, which can realize the fast vibration simulation of flexible supported gear system considering the coupling relationship between transmission system, housing, and isolation system. In order to obtain the dynamic parameters of bearing, Lin et al [4] identified the bearing stiffness and damping parameters through experimental modal analysis and least square method and built a coupled FE model of the gear-shaft-bearing-housing system to study the vibration and noise of gearbox. Vanhollebeke et al [5] combined a flexible multibody model and an acoustic model to compute the acoustic response for a wind turbine gearbox and identified the major contributors through a panel contribution analysis.…”
Section: Introductionmentioning
confidence: 99%